More than Just a Break from Treatment: How Substance Use Disorder Patients Experience the Stable Environment in Horse-Assisted Therapy - Ann Kern-Godal; Ida Halvorsen Brenna; Espen Ajo Arnevik; Edle Ravndal (SAGE Publishing, 2016)
Inclusion of horse-assisted therapy (HAT) in substance use disorder (SUD) treatment is rarely reported. Our previous studies show improved treatment retention and the importance of the patient-horse relationship. This qualitative study used thematic analysis, within a social constructionist framework, to explore how eight patients experienced contextual aspects of HAT's contribution to their SUD treatment. Participants described HAT as a "break from usual treatment". However, four interrelated aspects of this experience, namely "change of focus", "activity", "identity", and "motivation," suggest HAT is more than just a break from usual SUD treatment. The stable environment is portrayed as a context where participants could construct a positive self: one which is useful, responsible, and accepted; more fundamentally, a different self from the "patient/self" receiving treatment for a problem. The implications extend well beyond animal-assisted or other adjunct therapies. Their relevance to broader SUD policy and treatment practices warrants further study.